ANALISIS SEMANTIK “HORAS” SEBAGAI SIMBOL IDENTITAS BUDAYA BATAK TOBA - Junifer Siregar; Fransiska Risnawati Aritonang, Novellyn Debora Sitorus; Novellyn Debora Sitorus , Rista Veronika Nainggolan; Mei Pitriani Manurung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study attempts to uncover the semantic meaning of the term "Horas" as a symbol of the cultural identity of the Batak Toba people. The context of this study began with concerns about the declining awareness of the younger generation about the cultural meaning contained in traditional greetings. This study uses a qualitative descriptive approach using semantic analysis techniques that combine structural semantics and ethnolinguistic perspectives. Data were collected through comprehensive interviews with traditional spokespersons, supplemented by analysis of literature and cultural media. The findings of the study indicate that the term "Horas" not only signifies safety and well-being in the lexical sense, but also carries contextual meanings as prayers, blessings, spiritual support, and representations of social relationships. In various customary settings such as marriage, migration, death, and social events, "Horas" functions as a representation of noble values such as solidarity, respect, and family. The findings of this study emphasize that maintaining the important meaning of "Horas" is very important in order to uphold the cultural identity of the Batak Toba people and must be integrated through education and adaptive cultural media for future generations.